1997
DOI: 10.1111/j.1540-8167.1997.tb01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Child with Wolff‐Parkinson‐White Syndrome and Supraventricular Tachycardia:

Abstract: In the next decade, "better" management will be defined by cost effectiveness including morbidity, mortality, and cost. We used a cost-effectiveness model for children with Wolff-Parkinson-White syndrome (WPW) and supraventricular tachycardia (SVT) comparing medical, surgical, and catheter ablative treatment between age 5 years (estimated average age at first recurrence after infancy) and age 21. Charges were quantitated from actual hospital bills; mortality was estimated from the literature; morbidity was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…283,284 Catheter ablation of an atriofascicular (Mahaim) pathway is successful in preventing reentrant tachycardia in approximately 70% to 100% of patients. 285 Flecainide and propafenone are beneficial for the treatment of AVRT by directly slowing or blocking conduction over the pathway. These drugs are effective in approximately 85% to 90% of patients, with 30% reporting an absence of tachycardia.…”
Section: 271-275mentioning
confidence: 99%
“…283,284 Catheter ablation of an atriofascicular (Mahaim) pathway is successful in preventing reentrant tachycardia in approximately 70% to 100% of patients. 285 Flecainide and propafenone are beneficial for the treatment of AVRT by directly slowing or blocking conduction over the pathway. These drugs are effective in approximately 85% to 90% of patients, with 30% reporting an absence of tachycardia.…”
Section: 271-275mentioning
confidence: 99%
“…Garson and Kanter recently provided a cost effectiveness model for management of tachycardia 8. They compared the cost, morbidity, mortality, and efficacy of drug treatment, surgery, and radiofrequency ablation for a 5 year old child with symptomatic tachycardia associated with Wolff-Parkinson-White syndrome.…”
Section: Choice Of Treatmentmentioning
confidence: 99%
“…Cost/cost effectiveness Garson and Kanter [22] reported that in patients 5 to 21 years of age with Wolff-Parkinson-White syndrome and supraventricular tachycardia, the cost of catheter ablation was 39% of surgical management and 57% of medical management, with less overall morbidity and mortality.…”
Section: Interventional Proceduresmentioning
confidence: 99%